Oral Chinese Herbal Medicine plus usual care for diabetic kidney disease: study protocol for a randomized, double-blind, placebo-controlled pilot trial - Liu, Meifang; Di, Yuan Ming; Zhang, Lei; Yang, Lihong; Zhang, La; Chen, Junhui; Wang, Ruobing; Xie, Xiaoning; Lan, Fang; Xie, Liping; Huang, Juan; Zhang, Anthony Lin; et al. (Frontiers in Endocrinology, 2024)
Background: Diabetic kidney disease (DKD) has become the leading cause of kidney failure, causing a significant socioeconomic burden worldwide. The usual care for DKD fails to achieve satisfactory effects in delaying the persistent loss of renal function. A Chinese herbal medicine, Tangshen Qushi Formula (TQF), showed preliminary clinical benefits with a sound safety profile for people with stage 2-4 DKD. We present the protocol of an ongoing clinical trial investigating the feasibility, efficacy, and safety of TQF compared to placebo in delaying the progressive decline of renal function for people with stage 2-4 DKD.A mixed methods research design will be used in this study. A randomized, double-blind, placebo-controlled pilot trial will evaluate the feasibility, efficacy, and safety of TQF compared to